3D surround local sensing system H/W for intelligent excavation robot (IES) - Dong-Jun Yeom; Hyun-Seok Yoo; Young-Suk Kim (Journal of Asian Architecture and Building Engineering, 2019)
The recently developed intelligent excavation robot in Korea is a fully automated excavator equipped with global 3D modeling capabilities for an entire earthwork site and an intelligent task planning system. The intelligent excavation robot includes features such as autonomous driving, 3D surround modeling, autonomous excavation, loading, etc. An intelligent excavation robot features technology that allows for accurate recognition of objects near the excavator, including the terrain of surrounding environments, location of obstacles in the excavator’s path, and any approaching trucks and moving people. Such technology is critical to ensuring work quality and safety. In this study, we develop the hardware for a 3D surround laser sensing system that enables 3D image modeling of the terrain surrounding an intelligent excavation robot. By mounting a sensor onto an intelligent excavation robot, we conducted performance tests to determine the robot’s 3D modeling capabilities of the terrains and obstacles at an actual earthwork site. The experimental results are applied to an object recognition system for detecting the properties of the terrain of the workspace around the excavator, any approaching people, trucks, obstacles, etc. The proposed hardware includes a wide range of applications in the development of future automated construction equipment.